Ferromagnetism of MnAs studied by heteroepitaxial films on GaAs(001). - Das, A; Pampuch, C; Ney, A; Hesjedal, T; Däweritz, L; Koch, R; Ploog, K (2003)
Thin epitaxial films of MnAs--promising candidates for the spin injection into semiconductors--are well known to undergo simultaneously a first-order structural and magnetic phase transition at 10-40 degrees C. The evolution of stress and magnetization of MnAs/GaAs(001), both measured quantitatively with our cantilever beam magnetometer at the coexistence region of alpha-MnAs and beta-MnAs, reveal an orthorhombically distorted unit cell of the ferromagnetic phase, which provides important clues on the origin of ferromagnetism in MnAs.